THE INTERNAL SUPERVISION OF THE SCHOOL ADMINISTRATORS UNDER SARABURI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Tongyang, Voraphol; Vorapanya, Sermsap; Phayom, Choochart (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aimed to 1) study the level of internal supervision of school administrators under the Saraburi Primary Education Service Area Office 1. 2) compare the internal supervision of school administrators under the Saraburi Primary Education Service Area Office 1 based on their experience in school administration and school size. The sample group for the study consists of 300 administrators and teachers from schools under the Saraburi Primary Education Service Area Office 1 for the academic year 2024. The sample size was calculated using the Taro Yamane formula, and stratified random sampling was applied. A questionnaire was used as a tool for data collection, with a reliability coefficient of 0.980. The statistical methods used for data analysis included percentage, mean, standard deviation, one-way ANOVA, and pairwise comparisons using Scheffé’s method. The research results found that; 1) The overall level of internal supervision of school administrators under the Saraburi Primary Education Service Area Office 1 was high in all aspects. When broken down by aspect, the highest mean was in the area of supervision practices, followed by evaluation and reporting, internal supervision planning, assessing the current situation, problems, and needs, and the creation of media and tools, respectively. 2) When comparing internal supervision by school size, the overall results showed significant differences at the 0.05 level. However, when classified according to the administrators’ experience in school management, no significant differences were found.